Von Willebrand Factor as a Biological Sensor of Blood Flow to Monitor Percutaneous Aortic Valve Interventions. Issue 7 (27th March 2015) - Van Belle, Eric; Rauch, Antoine; Vincentelli, André; Jeanpierre, Emmanuelle; Legendre, Paulette; Juthier, Francis; Hurt, Christopher; Banfi, Carlo; Rousse, Natacha; Godier, Anne; Caron, Claudine; Elkalioubie, Ahmed; et al.
<x xml:space="preserve">Abstract</x> Rationale: Percutaneous aortic valve procedures are a major breakthrough in the management of patients with aortic stenosis. Residual gradient and residual aortic regurgitation are major predictors of midterm and long-term outcome after percutaneous aortic valve procedures. We hypothesized that (1) induction/recovery of high molecular weight (HMW) multimers of von Willebrand factor defect could be instantaneous after acute changes in blood flow, (2) a bedside point-of-care assay (platelet function analyzer-closure time adenine DI-phosphate [PFA-CADP]), reflecting HMW multimers changes, could be used to monitor in real-time percutaneous aortic valve procedures. Objective: To investigate the time course of HMW multimers changes in models and patients with instantaneous induction/reversal of pathological high shear and its related bedside assessment. Methods and Results: We investigated the time course of the induction/recovery of HMW multimers defects under instantaneous changes in shear stress in an aortic stenosis rabbit model and in patients undergoing implantation of a continuous flow left ventricular assist device. We further investigated the recovery of HMW multimers and monitored these changes with PFA-CADP in aortic stenosis patients undergoing transcatheter aortic valve implantation or balloon valvuloplasty. Experiments in the aortic stenosis rabbit model and in left ventricular assist device patients demonstrated that induction/recovery of HMW multimers occurs within 5 minutes. Transcatheter aortic valve implantation patients experienced an acute decrease in shear stress and a recovery of HMW multimers within minutes of implantation which was sustained overtime. In patients with residual high shear or with residual aortic regurgitation, no recovery of HMW multimers was observed. PFA-CADP profiles mimicked HMW multimers recovery both in transcatheter aortic valve implantation patients without aortic regurgitation (correction) and transcatheter aortic valve implantation patients with aortic regurgitation or balloon valvuloplasty patients (no correction). Conclusions: These results demonstrate that variations in von Willebrand factor multimeric pattern are highly dynamic, occurring within minutes after changes in blood flow. It also demonstrates that PFA-CADP can evaluate in real time the results of transcatheter aortic valve procedures.